Epigenetic drug discovery for Alzheimer's disease. (September 2014) - Cacabelos, Ramón; Torrellas, Clara
<x xml:space="preserve">Abstract</x> Introduction: It is assumed that epigenetic modifications are reversible and could potentially be targeted by pharmacological and dietary interventions. Epigenetic drugs are gaining particular interest as potential candidates for the treatment of Alzheimer's disease (AD). Areas covered: This article covers relevant information from over 50 different epigenetic drugs including: DNA methyltransferase inhibitors; histone deacetylase inhibitors; histone acetyltransferase modulators; histone methyltransferase inhibitors; histone demethylase inhibitors; non-coding RNAs (microRNAs) and dietary regimes. The authors also review the pharmacoepigenomics and the pharmacogenomics of epigenetic drugs. The readers will gain insight into i) the classification of epigenetic drugs; ii) the mechanisms by which these drugs might be useful in AD; iii) the pharmacological properties of selected epigenetic drugs; iv) pharmacoepigenomics and the influence of epigenetic drugs on genes encoding CYP enzymes, transporters and nuclear receptors; and v) the genes associated with the pharmacogenomics of anti-dementia drugs. Expert opinion: Epigenetic drugs reverse epigenetic changes in gene expression and might open future avenues in AD therapeutics. Unfortunately, clinical trials with this category of drugs are lacking in AD. The authors highlight the need for pharmacogenetic and pharmacoepigenetic studies to properly evaluate any efficacy and safety issues.